Assessment of Cota altissima (L.) J. Gay for phytochemical composition and antioxidant, anti-inflammatory, antidiabetic and antimicrobial activities - ŞEN, ALİ (WALTER DE GRUYTER GMBH, 2021)
Phytochemical profiles of essential oil (EO), fatty acids, and n-hexane (CAH), diethyl ether (CAD), ethyl acetate (CAE) and methanol extracts (CAM) of Cota altissima L. J. Gay (syn. Anthemis altissima L.) were investigated as well as their antioxidant, anti-inflammatory, antidiabetic and antimicrobial activites. The essential oil was characterized by the content of acetophenone (35.8%) and beta-caryophyllene (10.3%) by GC-MS/FID. Linoleic and oleic acid were found as main fatty acids. The major constituents of the extracts were found to be 5-caffeoylquinic acid, 3,5-dicaffeoylquinic acid, isorhamnetin glucoside, quercetin and quercetin glucoside by LC-MS/MS. Antioxidant activities of the extracts were determined by scavenging of DPPH and ABTS free radicals. Also, the inhibitory effects on lipoxygenase and alpha-glucosidase enzymes were determined. Antimicrobial activity was evaluated against Gram positive, Gram negative bacteria and yeast pathogens. CAM showed the highest antioxidant activity against DPPH and ABTS radicals with IC50 values of 126.60 and 144.40 mu g/mL, respectively. In the anti-inflammatory activity, CAE demonstrated the highest antilipoxygenase activity with an IC50 value of 105.40 mu g/mL, whereas, CAD showed the best inhibition of a-glucosidase with an IC50 value of 396.40 mu g/mL in the antidiabetic activity. CAH was effective against Staphylococcus aureus at MIC = 312.5 mu g/mL. This is the first report on antidiabetic, anti-inflammatory and antimicrobial activities of different extracts of C. altissima.
Keywords: activity; Cota altissima; essential oil; extract; GC-MS/FID; LC-MS/MS; CHEMICAL-COMPOSITION; ESSENTIAL OIL; ANTHEMIS-ALTISSIMA; INHIBITORY-ACTIVITIES; ACID; CLASSIFICATION; WIEDEMANNIANA; CHRYSANTHEMUM; CULTIVARS; PROFILES